Comparison of New Students Self-Confidence in Terms of Overseas Students and Non-migrants - Orny Novita Aluman; Dian Lestari Anakaka; Indra Yohanes Kiling (Lontar : Journal of Community Health, 2020)
Self-confidence is a feeling of confidence and a positive attitude for an individual that enables him/her to develop positive assessments, both for himself/herself and the environment or situation he/she is in. Overseas students need adjustments to provide an idea that they can be accepted well by the surrounding environment, whether they are newcomers to overseas students and non-migrants. This study aims to determine the differences in self-confidence of new students of the Psychology Study Program, Faculty of Public Health, Nusa Cendana University in terms of migrating and not migrating. This type of research is quantitative research. 73 new students who had migrated and did not migrate were randomly selected from four classes. The variables studied were tested using the independent sample t-test to determine differences in the confidence of new students in terms of migrating and not migrating. The results of the independent sample t-test stated that the confidence between new students in terms of migrating and not migrating the Psychology Study Program was not different, it was obtained from the significance results (2-tailed) of (0.478) (p> 0.05).